Peningkatan kesehatan gigi dan mulut melalui penerapan manajemen berbasis sekolah - Syahnur Said; Nur Fadhilah Arifin; Syamsiah Syam (DEDIKASI, 2019)
The Community Partnership Program (PKM) partners are SDN 96 Mannanti, Tellu Limpoe, Sinjai. The problem is: (1) The exchange rate of the rupiah against the US dollar is weakening which affects health costs (2) The high prevalence of dental caries which ranks fifth in the 10 most diseases (Data from the Mannanti Puskesmas Tellu Limpoe in 2017) (3). There is only one dentist in Mannanti village who only practices at the puskesmas. (4) Medical equipment especially dentistry tools at Mannanti puskesmas is limited. (5) Access to public transportation goes to Sinjai Hospital which is difficult and far enough (± 30 km distance and 60 minutes). (6) Public perception that dental examinations are expensive is also one of the reasons why someone is lazy to go to the dentist. The solutions offered from the PKM activities are: (a) Changing people's mindset from curative treatment shifting to promotive and preventive treatment so that the funds used are more minimum; (b) Implementation of SIKAPAMASE (SIkat gigi PAgi bersaMA di SEkolah) as an economical dental caries prevention program; (c) Application of topical fluor to students as an additional preventive measure to prevent cavities; (d) Guidance of teachers and parents as mediators of dental and oral health information to the community; (e) Healthy smile tooth ambassador competition for elementary students. The expected targets of the PKM activities are: (1) The caries status of SDN 96 Mannanti students reduced by 50% measured through the DMF-T index (def-t) measured through the results of pre-test and post-test activities; (2) Increasing students' knowledge about how to maintain dental health is measured through the results of pre-test and post-test activities; (3) Our program products are in the form of human resources, it is expected that SDN 96 students can be mediators of dental and oral health information in the family, school and home environment; (4) Caries preventive guidance booklet (5) Ambassador of healthy teeth. (6) SIKAPAMASE (SIkat gigi PAgi bersaMA di SEkolah) as an innovative program at the Mannanti health center that is carried out continuously.